Wear-resistant alloy material and preparation method thereof
By modifying the wear-resistant alloy material combined with molybdenum disulfide particles and DLC coating, the wear problem of aluminum-lithium alloy in high-speed rotating parts and harsh environments is solved, and excellent wear resistance and self-lubricating performance is achieved, and the material is extended. service life.
Patent Information
- Application Number
- CN202411647009.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Standard aluminum-lithium alloys are prone to wear and tear in high-speed rotating parts and harsh environments, resulting in failure of parts and shortened life, affecting equipment operation efficiency and increasing maintenance costs.
Wear-resistant alloy materials combined with modified molybdenum disulfide particles and diamond-like carbon (DLC) coating are used to modify the binding of molybdenum disulfide particles with aluminum lithium alloy matrix through coupling agent to increase adhesion and apply it to the surface. DLC coating, forming microporous structures to store lubricating oil, provides a dual lubrication mechanism.
It significantly improves the wear resistance and self-lubricating performance of the material, extends the lubrication effect, reduces the friction coefficient, and even maintains stable lubrication performance in high temperature and high pressure environments, extending the service life of the material.
Smart Images

Figure CN119220871A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy material manufacturing, and in particular relates to a wear-resistant alloy material and a preparation method thereof. Background Art
[0002] As a lightweight and high-strength material, aluminum-lithium alloy has been widely used in high-end manufacturing industries such as aerospace, automobiles, and ships that have strict weight requirements due to its low density, high elastic modulus, and good corrosion resistance. For example, in the field of aerospace, aluminum-lithium alloys are used to manufacture aircraft structural parts and satellite components, which not only reduces the weight of the aircraft, improves fuel efficiency, but also extends the service life of the aircraft. However, standard aluminum-lithium alloys have insufficient wear resistance in practical applications, especially in high-speed rotating parts, sliding contact surfaces, and other occasions that need to withstand high mechanical stress. Wear is prone to occur, resulting in part failure or shortened life, seriously affecting the operating efficiency of the equipment and increasing maintenance costs. Specifically, the wear problem of aluminum-lithium alloys in these key parts is particularly obvious. For example, in high-speed rotating parts such as aircraft engine blades, transmission shafts, and bearings, these parts are subject to great friction and wear due to long-term high-speed operation and frequent start-stop operations. Wear not only causes changes in the size and shape of parts, affecting their mechanical properties, but may also cause fatigue cracks, and ultimately lead to part breakage and failure. In addition, in the transmission, differential and suspension system of the car, aluminum-lithium alloy parts also face similar wear problems, especially in harsh working environments, such as high temperature, high humidity and corrosive media, the wear will be more serious. Therefore, based on the above problems, it is extremely necessary to develop a wear-resistant and corrosion-resistant aluminum alloy material. Summary of the invention
[0003] In view of the defects of the prior art, an object of the present invention is to provide a wear-resistant alloy material and a preparation method thereof.
[0004] The technical effect described in the present invention is achieved through the following technical scheme: a wear-resistant alloy material, whose composition includes a base alloy and a reinforcement phase material, the base alloy includes the following elements calculated by mass percentage: lithium 1.5-3wt%, magnesium 0.5-2.2wt%, copper 1.5-2.8wt%, manganese 0.25-0.45wt%, cadmium 0.1-0.5wt%, scandium 0.05-0.08wt%, unavoidable impurity elements less than or equal to 0.2wt%, and the balance is aluminum; the amount of the reinforcement phase material accounts for 1.5-5wt% of the base alloy material.
[0005] Preferably, the element composition of the matrix alloy is Al-Li-Cu-Mg-Mn.
[0006] Preferably, the reinforcement phase material comprises the following raw material composition in parts by mass: 40 to 50 parts of modified molybdenum disulfide particles, 20 to 30 parts of graphite, 10 to 20 parts of dibasic acid ester, and 0.2 to 0.3 parts of antioxidant.
[0007] Preferably, the antioxidant is any one of 2,6-di-tert-butyl-p-cresol, diphenylamine and N-phenyl-α-naphthylamine.
[0008] Preferably, the specific preparation steps of the modified molybdenum disulfide are as follows:
[0009] A1: Add acetylacetonate titanate to anhydrous ethanol, adjust the pH to 4-5 with 0.1M hydrochloric acid solution, and stir at 300rpm for 30-60min to obtain a 1-2wt% coupling agent solution; add molybdenum disulfide to anhydrous ethanol, perform ultrasonic treatment, and disperse evenly to obtain a 10wt% molybdenum disulfide dispersion;
[0010] A2: Slowly add the coupling agent solution prepared in step A1 to the molybdenum disulfide dispersion at a rate of 1-5 mL / min, continue stirring at room temperature for 2-4 hours, then centrifuge at 5000 rpm for 10 minutes, wash with anhydrous ethanol three times, and vacuum dry at 60°C for 12 hours to obtain modified molybdenum disulfide particles;
[0011] Preferably, in step A2, the volume ratio of the coupling agent solution to the molybdenum disulfide dispersion is 0.5 to 1:5.
[0012] Preferably, another aspect of the present invention is to provide a method for preparing a wear-resistant alloy material, and the specific preparation steps are as follows:
[0013] S1: weighing Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd, Al-Sc master alloy and pure Al according to the above raw material ratios;
[0014] S2: under the protection of high-purity argon, the pure Al in step S1 is added into a graphite crucible, the temperature is raised to 750-800° C. for melting, and then the Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd and Al-Sc master alloy in step S1 are added in sequence, the alloy is slowly stirred and uniformly dissolved, and degassing is performed to obtain a melt;
[0015] S3: cooling the melt prepared in step S2, and then slowly adding the modified molybdenum disulfide particles heated to 200° C. at a stirring speed of 300 rpm, and continuing stirring for 10 to 15 minutes to obtain a composite melt; cooling the composite melt to 700° C., preheating the casting mold to 150 to 200° C., and pouring the composite melt into the casting mold under the protection of a nitrogen atmosphere for casting. After the casting is completed, the casting is naturally cooled to room temperature;
[0016] S4: heating the casting prepared in step S3 to 520-540° C., maintaining the temperature for 2-4 hours, and then rapidly quenching to room temperature and performing aging treatment to obtain a composite material;
[0017] S5: polishing the composite material prepared in step S4, ultrasonically treating it with anhydrous ethanol at 200W for 15 minutes, and fixing it on a vacuum sample table after natural drying, introducing argon gas, adjusting the deposition parameters, and the DLC coating deposition thickness is 1 to 3 μm. After the deposition is completed, annealing is performed at 200°C for 2 hours under vacuum to obtain a coating composite material;
[0018] S6: Add an antioxidant to the dibasic ester, stir and mix evenly to obtain lubricating oil, add the coating composite material prepared in step S5 to a vacuum impregnation device, evacuate to -0.08 MPa, maintain for 30 minutes, slowly add lubricating oil, restore to normal pressure, treat for 15 to 30 minutes, then gently wash with anhydrous ethanol, and let stand at room temperature for 12 hours to obtain an alloy material.
[0019] Preferably, in step S2, the degassing treatment is to introduce argon gas and stand for 10 to 15 minutes;
[0020] Preferably, in step S3, the melt cooling temperature is 720°C;
[0021] Preferably, in step S4, the aging treatment is to heat the quenched material to 150-180° C. and keep the temperature for 10-15 hours;
[0022] Preferably, in step S5, the roughness of the polishing treatment needs to reach Ra 0.1μm; the deposition parameters are CH4 flow rate 20sccm, H2 flow rate 5-10sccm, N2 flow rate 2-5sccm, and pressure control 0.5-1Pa; the DLC coating deposition parameters are substrate temperature 200°C, pulse voltage -600V, and pulse frequency 1000Hz.
[0023] The beneficial effects of the present invention are as follows:
[0024] The present invention utilizes a coupling agent to modify molybdenum disulfide (MoS2) particles, significantly enhancing the bonding force between the particles and the aluminum-lithium alloy matrix, promoting the uniform dispersion of the particles in the matrix, and preventing agglomeration and local wear; the enhanced adhesion reduces the shedding of particles during the friction process, prolongs the duration of the lubrication effect, and reduces the surface wear caused by the loss of particles. A diamond-like carbon (DLC) coating with a hardness close to that of natural diamond is applied to the alloy surface to provide excellent wear resistance; even under high stress conditions, the coating can still remain intact to protect the matrix material; as the DLC coating wears, the MoS2 particles in the lower layer are gradually exposed, releasing lubricating components, taking over the lubrication function of the coating, and prolonging the lubrication effect through the synergistic effect of coating wear and particle release. A micron-level pore structure is introduced into the nano coating to effectively store lubricating oil; during the friction process, due to the increase in temperature or contact pressure, the lubricating oil is gradually released from the micropores, forming a thin oil film on the surface, providing instant lubrication, and the slow release of the lubricating oil reduces the temperature of the friction interface, reduces the thermal deformation of the material caused by friction heat, and thus prolongs the service life of the DLC coating. The microporous structure can also effectively relieve local stress concentration, prevent the formation and expansion of coating cracks, enhance overall toughness, and reduce the risk of spalling. High-temperature stable lubricants, combined with antioxidants and anti-wear additives, can resist decomposition caused by friction heat, inhibit oxidation and degradation in high-temperature environments, and form an anti-wear protective film on the friction surface, which can maintain low friction even under high temperature and high friction conditions. Under this dual lubrication mechanism, the lubricating oil in the micropores and the gradually exposed MoS2 particles work together to significantly reduce the friction coefficient under different working conditions, so that the material maintains a low friction state during start-up, stop and continuous friction; the lubricating oil is suitable for lower temperatures and medium pressures, while the MoS2 particles perform well under high temperatures and high pressures, so that the material maintains excellent lubrication properties over a wide range of temperatures and pressures. The DLC coating provides high strength and wear protection when intact; when gradually worn, it relies on the slow release of solid lubricants and lubricating oils to continuously maintain the lubrication of the friction surface; the slow release of lubricating oils and the staged release of solid lubricants prevent the rapid consumption of lubricants and significantly extend the wear life of the material. Modified MoS2 particles, DLC coating, microporous structure and high-temperature stable lubricant synergistically enhance the wear resistance and self-lubricating properties of the material. Even in extremely high temperature and high pressure environments, the material can maintain a stable and long-lasting lubrication effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1is a graph showing the wear resistance test results of the alloy materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4;
[0027] Figure 2 It is a graph showing the self-lubricating performance test results of the alloy materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0029] Embodiment 1: A wear-resistant alloy material, comprising a matrix alloy and a reinforcement phase material, wherein the matrix alloy comprises the following elements calculated by mass percentage: 1.5wt% lithium, 0.5wt% magnesium, 1.5wt% copper, 0.25wt% manganese, 0.1wt% cadmium, 0.05wt% scandium, unavoidable impurity elements less than or equal to 0.2wt%, and the balance being aluminum; the reinforcement phase material accounts for 1.5wt% of the matrix alloy material.
[0030] The element composition of the matrix alloy is Al-Li-Cu-Mg-Mn.
[0031] The reinforcement phase material comprises the following raw materials in parts by mass: 40 parts of modified molybdenum disulfide particles, 20 parts of graphite, 10 parts of dibasic acid ester, and 0.2 parts of antioxidant.
[0032] The specific preparation steps of modified molybdenum disulfide are as follows:
[0033] A1: 1g of acetylacetonate titanate was added to 50mL of anhydrous ethanol, and the pH was adjusted to 5 with 0.1M hydrochloric acid solution. The mixture was stirred at 300rpm for 30min to obtain a 1wt% coupling agent solution. 50g of molybdenum disulfide was added to 500mL of anhydrous ethanol, and the mixture was dispersed evenly with ultrasonic treatment to obtain a 10wt% molybdenum disulfide dispersion.
[0034] A2: 50 mL of the coupling agent solution prepared in step A1 was slowly added dropwise to 500 mL of the molybdenum disulfide dispersion at a rate of 1 mL / min, and stirred continuously at room temperature for 5 h, and then centrifuged at 5000 rpm for 10 min, and washed three times with anhydrous ethanol, and vacuum dried at 60°C for 12 h to obtain modified molybdenum disulfide particles;
[0035] The specific preparation steps of wear-resistant alloy materials are as follows:
[0036] S1: weighing Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd, Al-Sc master alloy and pure Al according to the above raw material ratios;
[0037] S2: under the protection of high-purity argon, the pure Al in step S1 is added into a graphite crucible, the temperature is raised to 750° C. to melt, and then the Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd and Al-Sc master alloy in step S1 are added in sequence, slowly stirred to uniformly dissolve, argon is introduced and the mixture is allowed to stand for 10 minutes for degassing to obtain a melt;
[0038] S3: cooling the melt prepared in step S2, and then slowly adding the modified molybdenum disulfide particles heated to 200°C at a stirring speed of 300 rpm, and continuing stirring for 10 minutes to obtain a composite melt; cooling the composite melt to 700°C, preheating the casting mold to 150°C, and pouring the composite melt into the casting mold under the protection of a nitrogen atmosphere for casting. After the casting is completed, the casting is naturally cooled to room temperature;
[0039] S4: heating the casting prepared in step S3 to 520° C., maintaining the temperature for 2 hours, and then rapidly quenching the casting to room temperature, heating the quenched casting to 150° C., and maintaining the temperature for 10 hours to obtain a composite material;
[0040] S5: polishing the composite material prepared in step S4 to a roughness of Ra 0.1 μm, then ultrasonically treating it with anhydrous ethanol at 200W for 15 minutes, and fixing it on a vacuum sample table after natural drying, introducing argon gas, adjusting the deposition parameters to a CH4 flow rate of 20 sccm, a H2 flow rate of 5 sccm, a N2 flow rate of 2 sccm, and a pressure control of 0.5 Pa; the DLC coating deposition parameters are substrate temperature of 200°C, pulse voltage of -600V, pulse frequency of 1000Hz, and DLC coating deposition thickness of 1 μm. After the deposition is completed, annealing is performed at 200°C for 2 hours under vacuum to obtain a coating composite material;
[0041] S6: Add 2,6-di-tert-butyl-p-cresol to the dibasic ester, stir and mix evenly to obtain lubricating oil, add the coating composite material prepared in step S5 to the vacuum impregnation equipment, evacuate to -0.08 MPa, maintain for 30 minutes, slowly add lubricating oil, restore to normal pressure, treat for 15 minutes, and then gently wash with anhydrous ethanol, let stand at room temperature for 12 hours to obtain the alloy material.
[0042] Example 2: A wear-resistant alloy material, comprising a base alloy and a reinforcement phase material, wherein the base alloy comprises the following elements calculated in mass percentage: 2.5wt% lithium, 1.5wt% magnesium, 2.8wt% copper, 0.45wt% manganese, 0.5wt% cadmium, 0.08wt% scandium, unavoidable impurity elements less than or equal to 0.2wt%, and the balance being aluminum; the reinforcement phase material accounts for 5wt% of the base alloy material.
[0043] The element composition of the matrix alloy is Al-Li-Cu-Mg-Mn.
[0044] The reinforcement phase material comprises the following raw materials in parts by mass: 45 parts of modified molybdenum disulfide particles, 25 parts of graphite, 15 parts of dibasic acid ester, and 0.25 parts of antioxidant.
[0045] The specific preparation steps of modified molybdenum disulfide are as follows:
[0046] A1: 2 g of acetylacetonate titanate was added to 100 mL of anhydrous ethanol, the pH was adjusted to 4 with 0.1 M hydrochloric acid solution, and the reaction was stirred at 300 rpm for 60 min to obtain a 2 wt% coupling agent solution; 50 g of molybdenum disulfide was added to 500 mL of anhydrous ethanol, ultrasonically treated, and dispersed uniformly to obtain a 10 wt% molybdenum disulfide dispersion;
[0047] A2: 100 mL of the coupling agent solution prepared in step A1 was slowly added dropwise to 500 mL of the molybdenum disulfide dispersion at a rate of 2 mL / min, and the mixture was stirred continuously for 3 h at room temperature, and then centrifuged at 5000 rpm for 10 min, and washed three times with anhydrous ethanol, and vacuum dried at 60°C for 12 h to obtain modified molybdenum disulfide particles;
[0048] The specific preparation steps of wear-resistant alloy materials are as follows:
[0049] S1: weighing Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd, Al-Sc master alloy and pure Al according to the above raw material ratios;
[0050] S2: under the protection of high-purity argon, the pure Al in step S1 is added into a graphite crucible, the temperature is raised to 800° C. to melt, and then the Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd and Al-Sc master alloy in step S1 are added in sequence, slowly stirred to uniformly dissolve, argon is introduced and the mixture is allowed to stand for 15 minutes for degassing to obtain a melt;
[0051] S3: cooling the melt prepared in step S2, and then slowly adding the modified molybdenum disulfide particles heated to 200°C at a stirring speed of 300 rpm, and continuing stirring for 12 minutes to obtain a composite melt; cooling the composite melt to 700°C, preheating the casting mold to 200°C, and pouring the composite melt into the casting mold under the protection of a nitrogen atmosphere for casting. After the casting is completed, the casting is naturally cooled to room temperature;
[0052] S4: heating the casting prepared in step S3 to 540° C., maintaining the temperature for 3 hours, and then rapidly quenching the casting to room temperature, heating the quenched casting to 180° C., and maintaining the temperature for 15 hours to obtain a composite material;
[0053] S5: polishing the composite material prepared in step S4 to a roughness of Ra 0.1 μm, then ultrasonically treating it with anhydrous ethanol at 200W for 15 minutes, naturally drying it, fixing it on a vacuum sample table, introducing argon gas, adjusting the deposition parameters to a CH4 flow rate of 20 sccm, a H2 flow rate of 10 sccm, a N2 flow rate of 5 sccm, and a pressure control of 1 Pa; the DLC coating deposition parameters are substrate temperature of 200°C, pulse voltage of -600V, pulse frequency of 1000Hz, and a DLC coating deposition thickness of 3 μm. After the deposition is completed, annealing is performed at 200°C for 2 hours under vacuum to obtain a coating composite material;
[0054] S6: Add N-phenyl-α-naphthylamine to the dibasic ester, stir and mix evenly to obtain lubricating oil, add the coating composite material prepared in step S5 to the vacuum impregnation equipment, evacuate to -0.08MPa, maintain for 30 minutes, slowly add lubricating oil, restore to normal pressure, treat for 30 minutes, and then gently wash with anhydrous ethanol, let stand at room temperature for 12 hours to obtain the alloy material.
[0055] Example 3: A wear-resistant alloy material, comprising a base alloy and a reinforcement phase material, wherein the base alloy comprises the following elements calculated in mass percentage: 3wt% lithium, 2.2wt% magnesium, 2.5wt% copper, 0.4wt% manganese, 0.3wt% cadmium, 0.06wt% scandium, unavoidable impurity elements less than or equal to 0.2wt%, and the balance being aluminum; the reinforcement phase material accounts for 3.5wt% of the base alloy material.
[0056] The element composition of the matrix alloy is Al-Li-Cu-Mg-Mn.
[0057] The reinforcement phase material comprises the following raw materials in parts by mass: 50 parts of modified molybdenum disulfide particles, 30 parts of graphite, 20 parts of dibasic acid ester, and 0.3 parts of antioxidant.
[0058] The specific preparation steps of modified molybdenum disulfide are as follows:
[0059] A1: 1.5 g of acetylacetonate titanate was added to 100 mL of anhydrous ethanol, the pH was adjusted to 4.5 with 0.1 M hydrochloric acid solution, and the reaction was stirred at 300 rpm for 50 min to obtain a 1.5 wt% coupling agent solution; 50 g of molybdenum disulfide was added to 500 mL of anhydrous ethanol, ultrasonically treated, and dispersed uniformly to obtain a 10 wt% molybdenum disulfide dispersion;
[0060] A2: 75 mL of the coupling agent solution prepared in step A1 was slowly added dropwise to 500 mL of molybdenum disulfide dispersion at a rate of 5 mL / min, and stirred continuously at room temperature for 2 h, and then centrifuged at 5000 rpm for 10 min, and washed three times with anhydrous ethanol, and vacuum dried at 60°C for 12 h to obtain modified molybdenum disulfide particles;
[0061] The specific preparation steps of wear-resistant alloy materials are as follows:
[0062] S1: weighing Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd, Al-Sc master alloy and pure Al according to the above raw material ratios;
[0063] S2: under the protection of high-purity argon, the pure Al in step S1 is added into a graphite crucible, the temperature is raised to 780° C. to melt, and then the Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd and Al-Sc master alloy in step S1 are added in sequence, slowly stirred to uniformly dissolve, argon is introduced and the mixture is allowed to stand for 12 minutes for degassing to obtain a melt;
[0064] S3: cooling the melt prepared in step S2, and then slowly adding the modified molybdenum disulfide particles heated to 200°C at a stirring speed of 300 rpm, and continuing stirring for 15 minutes to obtain a composite melt; cooling the composite melt to 700°C, preheating the casting mold to 180°C, and pouring the composite melt into the casting mold under the protection of a nitrogen atmosphere for casting. After the casting is completed, the casting is naturally cooled to room temperature;
[0065] S4: heating the casting prepared in step S3 to 530° C., maintaining the temperature for 4 hours, and then rapidly quenching the casting to room temperature, heating the quenched casting to 160° C., and maintaining the temperature for 12 hours to obtain a composite material;
[0066] S5: polishing the composite material prepared in step S4 to a roughness of Ra 0.1 μm, then ultrasonically treating it with anhydrous ethanol at 200W for 15 minutes, naturally drying it, fixing it on a vacuum sample table, introducing argon gas, adjusting the deposition parameters to a CH4 flow rate of 20 sccm, a H2 flow rate of 8 sccm, a N2 flow rate of 3 sccm, and a pressure control of 0.8 Pa; the DLC coating deposition parameters are substrate temperature of 200°C, pulse voltage of -600V, pulse frequency of 1000Hz, and a DLC coating deposition thickness of 2 μm. After the deposition is completed, annealing is performed at 200°C for 2 hours under vacuum to obtain a coating composite material;
[0067] S6: Add diphenylamine to the dibasic ester, stir and mix evenly to obtain lubricating oil, add the coating composite material prepared in step S5 to the vacuum impregnation equipment, evacuate to -0.08MPa, maintain for 30 minutes, slowly add lubricating oil, restore to normal pressure, treat for 20 minutes, and then gently wash with anhydrous ethanol, let stand at room temperature for 12 hours to obtain the alloy material.
[0068] Comparative Example 1: The operation of Comparative Example 1 is basically the same as that of Example 2, except that unmodified MoS2 particles are used to replace the modified MoS2 particles in Comparative Example 1.
[0069] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that no DLC coating is applied and no microporous structure is present in Comparative Example 2.
[0070] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that in Comparative Example 3, no microporous structure is imparted and no lubricating oil is added.
[0071] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that in Comparative Example 4, a microporous structure is imparted but no lubricating oil is added.
[0072] Performance Test:
[0073] The density of the alloy materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested by the volume method; the elongation, tensile strength and yield strength of the alloy materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested by a universal material testing machine. The results are shown in Table 1 below:
[0074] Table 1. Density, elongation, tensile strength and yield strength properties of the alloy materials of Examples 1 to 3 and Comparative Examples 1 to 4
[0075]
[0076] It can be seen from the results in Table 1 that the alloy material prepared by the present invention has excellent elongation, tensile strength and yield strength, and excellent mechanical properties; it can be seen from the results of Comparative Example 1 and Example 2 that the unmodified MoS2 particles are easy to agglomerate to form concentrated defects, which may become the starting points of cracks under stress, thereby reducing the elongation and tensile strength of the material. In addition, the bonding force between the unmodified MoS2 particles and the matrix alloy is low, and the particles are more likely to fall off during the stretching process, weakening the overall strength and toughness of the material; it can be seen from the results of Comparative Example 2 and Example 2 that the DLC coating mainly improves the surface wear resistance and has little effect on the overall mechanical properties; the lack of coating protection makes the material surface more susceptible to Micro cracks and defects are generated, which may lead to a slight decrease in elongation; from the results of Comparative Example 3 and Example 2, it can be seen that the lack of lubricating oil has limited effect on the mechanical properties of the material, and the elongation and strength are still maintained in a high range, while the lack of sustained release of lubricating oil reduces the lubrication performance during friction, which may lead to stress concentration, and then lead to a slight decrease in elongation; from the results of Comparative Example 4 and Example 2, it can be seen that the microporous structure helps to alleviate stress concentration and improve the crack resistance of the coating, but the lack of lubricating oil filling cannot play the role of lubrication and sustained release; in addition, the presence of the microporous structure may slightly reduce the density of the coating. Due to the absence of lubricating oil, the internal stress of the coating may increase, which leads to a decrease in elongation.
[0077] Wear resistance test: The wear resistance of the alloy materials prepared in Example 2 and Comparative Examples 1 to 4 was tested by a high temperature ball-disc friction and wear tester. The test temperatures were divided into 25°C, 100°C, 200°C and 400°C, and the wear rate (mm 3 / N·m), the results are as follows Figure 1 shown.
[0078] Depend on Figure 1The results show that the alloy material prepared by the present invention has excellent wear resistance and good wear resistance at higher temperatures. The lubricating oil provides excellent instantaneous lubrication. After the lubricating oil is completely released, a protective film is formed on the DLC coating, which effectively delays the wear of the DLC coating. From the results of Example 2 and Comparative Example 1, it can be seen that the unmodified MoS2 particles have poor adhesion to the substrate and may partially fall off during the friction process, resulting in increased local wear. Due to the effects of the DLC coating and the lubricating oil, excellent wear resistance is provided at lower temperatures, while the wear resistance is significantly affected at higher temperatures. From the results of Example 2 and Comparative Example 2, it can be seen that the substrate material is directly exposed due to the lack of the DLC coating. The wear resistance is affected, there is a lack of immediate lubrication, the friction coefficient is high, and friction heat accumulates, resulting in increased wear, and the wear resistance is significantly affected; from the results of Example 2 and Comparative Example 3, it can be seen that there is a DLC coating but no microporous structure and lubricating oil, the friction coefficient is high, the coating may accelerate wear under high friction, and the modified MoS2 particles are gradually exposed and begin to provide lubrication, but due to the lack of synergistic effect of lubricating oil, the lubrication and wear resistance are significantly affected; from the results of Example 2 and Comparative Example 4, it can be seen that the microporous structure reduces the stress concentration in the coating to a certain extent, effectively prevents crack formation and expansion, and enhances the toughness of the coating, but lacks lubricating oil and cannot provide immediate lubrication, and the wear resistance is affected to a certain extent.
[0079] Self-lubricating performance test: The alloy materials prepared in Example 2 and Comparative Examples 1 and 4 were fixed on a friction tester. The test sample was a disc with a diameter of 50 mm and a thickness of 5 mm. A load of 20 N and a speed of 0.1 m / s were used at 100° C. The test was conducted for 120 min. Samples were taken at 10 min, 20 min, 40 min, 60 min and 120 min, respectively. The lubricating oil release rate (mg / min) was calculated as follows: (mass before test - mass after test) / interval time. The results are shown in FIG. Figure 2 shown.
[0080] Depend on Figure 2 The results show that the composite effect of the microporous structure of the alloy material prepared by the present invention and the coating can maintain a stable release efficiency for a long time; from the results of Comparative Example 1 and Example 2, it can be seen that the unmodified MoS2 particles may cause the unevenness and defects of the microporous structure of the coating, which in turn leads to the initial too fast release of lubricating oil, and then the release efficiency drops rapidly; from the results of Example 2 and Comparative Example 4, it can be seen that the mass loss in Comparative Example 4 is mainly due to material wear, but the loss is extremely low and can be ignored.
[0081] Corrosion resistance test: The alloy materials prepared in Example 2 and Comparative Examples 1 to 4 were tested in a 5% NaCl solution at a temperature of 35±2°C for 168h, and the appearance changes were recorded. The results are shown in Table 2 below.
[0082] Table 2. Salt spray corrosion test results of alloy materials prepared in Example 2 and Comparative Examples 1 to 4
[0083]
[0084]
[0085] It can be seen from the results in Table 3 that the alloy material prepared by the present invention has excellent corrosion resistance. It can be seen from the results of Comparative Example 1 and Example 2 that the unmodified MoS2 particles are poorly bonded to the matrix, which may lead to the formation of tiny defects inside the material, resulting in a decrease in corrosion resistance; it can be seen from the results of Comparative Example 2 and Example 2 that the alloy material loses its main barrier protection due to the lack of DLC coating and microporous structure, and the absence of lubricating oil, and is easily corroded in a corrosive environment, and its corrosion resistance is significantly affected; it can be seen from the results of Comparative Example 3 and Example 2 that the DLC coating provides certain corrosion resistance, but lacks the sustained release effect of lubricating oil, and microcracks are easily formed, which leads to a slight decrease in corrosion resistance; it can be seen from the results of Comparative Example 4 and Example 2 that although the DLC coating provides certain corrosion resistance, due to the lack of lubricating oil filling in the microporous structure, the corrosive medium is easy to penetrate, and the corrosion resistance is affected to a certain extent.
[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant alloy material, characterized in that: The alloy material composition includes a base alloy and a reinforcement phase material. The base alloy includes the following elements calculated by mass percentage: 1.5-3wt% lithium, 0.5-2.2wt% magnesium, 1.5-2.8wt% copper, 0.25-0.45wt% manganese, 0.1-0.5wt% cadmium, 0.05-0.08wt% scandium, unavoidable impurity elements less than or equal to 0.2wt%, and the balance is aluminum; the reinforcement phase material accounts for 1.5-5wt% of the base alloy material.
2. A wear-resistant alloy material according to claim 1, characterized in that: The reinforcing phase material comprises the following raw materials in parts by mass: 40 to 50 parts of modified molybdenum disulfide particles, 20 to 30 parts of graphite, 10 to 20 parts of dibasic acid ester, and 0.2 to 0.3 parts of antioxidant.
3. A wear-resistant alloy material according to claim 2, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-p-cresol, diphenylamine and N-phenyl-α-naphthylamine.
4. A wear-resistant alloy material according to claim 3, characterized in that: The specific preparation steps of the modified molybdenum disulfide are as follows: A1: Add acetylacetonate titanate to anhydrous ethanol, adjust the pH with hydrochloric acid solution, stir and react to obtain a coupling agent solution; add molybdenum disulfide to anhydrous ethanol, perform ultrasonic treatment, and disperse evenly to obtain a molybdenum disulfide dispersion; A2: Slowly drop the coupling agent solution prepared in step A1 into the molybdenum disulfide dispersion, continue stirring at room temperature, then centrifuge, repeatedly wash with anhydrous ethanol, and vacuum dry to obtain modified molybdenum disulfide particles; in step A2, the volume ratio of the coupling agent solution to the molybdenum disulfide dispersion is 0.5 to 1:
5.
5. A method for preparing a wear-resistant alloy material according to any one of claims 1 to 4, characterized in that: The specific preparation steps are as follows: S1: weighing Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd, Al-Sc master alloy and pure Al according to the above raw material ratios; S2: under the protection of high-purity argon, the pure Al in step S1 is added into a graphite crucible, the temperature is raised to 750-800° C. for melting, and then the Al-Li master alloy, pure Mg, pure Cu, Al-Mn master alloy, pure Cd and Al-Sc master alloy in step S1 are added in sequence, the alloy is slowly stirred and uniformly dissolved, and degassing is performed to obtain a melt; S3: cooling the melt prepared in step S2, and then slowly adding the heated modified molybdenum disulfide particles under continuous stirring, and continuing stirring to obtain a composite melt; cooling the composite melt, preheating the casting mold, and pouring the composite melt into the casting mold under the protection of a nitrogen atmosphere for casting. After the casting is completed, the casting is naturally cooled to room temperature; S4: heating the casting prepared in step S3 to 520-540° C., maintaining the temperature for 2-4 hours, and then rapidly quenching to room temperature and performing aging treatment to obtain a composite material; S5: polishing the composite material prepared in step S4, ultrasonically treating it with anhydrous ethanol, and fixing it on a vacuum sample table after natural drying, introducing argon gas, adjusting the deposition parameters, and depositing the DLC coating with a thickness of 1 to 3 μm. After the deposition is completed, annealing is performed under vacuum to obtain a coating composite material; S6: adding an antioxidant to the dibasic acid ester, stirring and mixing to obtain lubricating oil, adding the coating composite material prepared in step S5 to a vacuum impregnation device, evacuating, maintaining, slowly adding lubricating oil, restoring to normal pressure, treating for 15 to 30 minutes, and then gently washing with anhydrous ethanol, standing at room temperature to obtain an alloy material.
6. A method for preparing the wear-resistant alloy material according to claim 5, characterized in that: In step S2, the degassing treatment is to introduce argon gas and leave it to stand for 10 to 15 minutes.
7. A method for preparing the wear-resistant alloy material according to claim 6, characterized in that: In step S4, the aging treatment is to heat the quenched material to 150-180° C. and keep the temperature for 10-15 hours.
8. A method for preparing the wear-resistant alloy material according to claim 7, characterized in that: In step S5, the roughness of the polishing treatment needs to reach Ra 0.1μm; the deposition parameters are CH4 flow rate 20sccm, H2 flow rate 5-10sccm, N2 flow rate 2-5sccm, and pressure control 0.5-1Pa; the DLC coating deposition parameters are substrate temperature 200°C, pulse voltage -600V, and pulse frequency 1000Hz.
